Reproductive Biology of Two Species Spiny Lobster in Donggala Waters Central Sulawesi - Nurdin, Muh. Saleh; Hasanah, Nur; Serdiati, Novalina; Putra, Aswad Eka (Universitas Negeri Semarang, 2024)
Spiny lobster species Panulirus versicolor and P. femoristriga in Donggala waters are reported to experience growth overfishing and recruitment overfishing. If this phenomenon continues, it will gradually reduce the spiny lobster population and result in an overall population decline. Information on reproductive biology is needed in the formulation of management and conservation policies for spiny lobsters in Donggala Waters, Central Sulawesi Province. The purpose of this study was to compare and analyze aspects of reproductive biology such as sex ratio, length-weight relationship, and spiny lobster condition factors. The research was conducted from July to December 2020 in the waters of Kabonga Village, Banawa Subdistrict, and Limboro Village, Central Banawa Subdistrict, Donggala District, Central Sulawesi Province. Reproductive biology data analysis applies several analytical models such as Chi-square, linear regression, Fulton condition factor, and Withney-Mann Test. The results showed no difference in sex ratio (balanced population) with negative allometric growth pattern and Fulton's condition factor in good condition (wellbeing) throughout the study in both P. versicolor and P. femoristriga. Population balance is important to ensure the continuity of recruitment, which is supported by adequate food availability, thus maintaining the stability of the spiny lobster population.